2012
DOI: 10.1159/000339026
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fibroblast Growth Factor 23 with Left Ventricle Mass Index and Coronary Calcificaton in Chronic Renal Disease

Abstract: Background: to evaluate the relationship between FGF23 and changes in biochemical parameters, left ventricle mass index, coronary, aortic and, valve calcifications. Methods: Totally 185 patients with chronic renal disease were included in this prospective, cross-sectional study. The patients were stratified according to GFR levels (mL/min/1.73m2) into 5 groups: ≥60, 45-59, 30-44, 15-29 and <15 (group 1-5 respectively).Biochemical parameters, serum FGF23 levels were measured. Echocardiographic assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Also, can FGF23 directly alter intracellular Ca 2ϩ ([Ca 2ϩ ] i ) and cardiac contractility? Previous studies have found a clinical association between FGF23 and LV mass (22,35,52) as well as declines in cardiac performance as measured by reduction in ejection fraction (19). However, to date no investigation has determined whether FGF23 can alter cardiac function independent of changes in cardiac hypertrophy.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Also, can FGF23 directly alter intracellular Ca 2ϩ ([Ca 2ϩ ] i ) and cardiac contractility? Previous studies have found a clinical association between FGF23 and LV mass (22,35,52) as well as declines in cardiac performance as measured by reduction in ejection fraction (19). However, to date no investigation has determined whether FGF23 can alter cardiac function independent of changes in cardiac hypertrophy.…”
mentioning
confidence: 97%
“…Although an endocrine axis has been established between bone and kidney, a new paradigm is emerging in which FGF23 could be important in establishing an endocrine axis between bone and heart. Circulating levels of FGF23 are markedly elevated 100-to 1,000-fold in patients with chronic kidney disease (CKD) (24, 31) and are independently associated with cardiovascular morbidity and mortality (8,22,26,34,35,48,52). Specifically, an association between left ventricular (LV) hypertrophy and serum FGF23 levels has been established in CKD patients (20,36,52).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous histological studies support the role of FGF23 in vascular calcification 15) ; serum FGF-23 concentrations were significantly associated with the degree of atheroma calcification 16) , and calcium deposition was correlated with FGF23 immunoreactivity in the coronary artery of the explanted heart 17) . Using multidetector computed tomography (MDCT), the potential association between FGF23 and CAC and/or AVC has also been clinically examined [18][19][20] , albeit with inconsistent results. However, the possibility remains that hyperphosphatemia rather than the FGF-23 level is the major factor driving vascular calcification 21) , which may also be indicated by the finding that FGF23 was not associated with arterial calcification and does not promote calcification 22) .…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…However, the possibility remains that hyperphosphatemia rather than the FGF-23 level is the major factor driving vascular calcification 21) , which may also be indicated by the finding that FGF23 was not associated with arterial calcification and does not promote calcification 22) . To evaluate the clinical utility of serum FGF23/ -Klotho for the detection or management of CAC/ AVC, various confounders, including calcium, phosphate, parathyroid hormone (PTH), and 1,25(OH)2D, should be considered, as observed in several recent studies 20,23) . To this end, in the current study, we investigated whether FGF23/ -Klotho levels are independently related with CAC/AVC calculated from image data obtained by 320-row MDCT.…”
Section: Patient Characteristicsmentioning
confidence: 99%